Guhong Injection Protects Against Apoptosis in Cerebral Ischemia by Maintaining Cerebral Microvasculature and Mitochondrial Integrity Through the PI3K/AKT Pathway - Zhou, Huifen; He, Yu; Zhu, Jiaqi; Lin, Xiaojie; Chen, Juan; Shao, Chongyu; Wan, Haitong; Yang, Jiehong (Frontiers in Pharmacology, 2021)
Guhong injection (GHI) can be used for the treatment of ischemic stroke. We investigated the anti-apoptosis, activity of GHI, its ability to repair the cerebral microvessels and mitochondria, and the PI3K/AKT signaling pathway of GHI against cerebral ischemia. Western blot and immunohistochemical analysis were used to determine the expression of cleaved-caspase-3, B-cell lymphoma-2 (Bcl-2), cytochrome c (Cyt-c), basic fibroblast growth factor (BFGF), vascular endothelial growth factor (VEGF), transforming growth factor-β1 (TGF-β1), and proteins in the PI3K/AKT signaling pathway. Transmission electron microscopy and scanning electron microscopy were used to evaluate the structures of the cerebral microvasculature and cells. Hoechst 33342 staining was used to evaluate the nuclear morphology. FITC-AV/PI double staining was used to measure the anti-apoptotic effects. The fluorescent dye JC-1 was used to measure mitochondrial membrane potential. Enzyme-linked immunosorbent assay (ELISA) was used to detect the activities of matrix metalloproteinase-9 (MMP-9). Biochemical assay kits were used to detect the activities of lactate dehydrogenase (LDH), superoxide dismutase (SOD), and malondialdehyde (MDA). Compared with the middle cerebral artery occlusion (MCAO) group, there was decreased infarct volume and significantly improved neurological deficits in the GHI group. In addition, the expression of Bcl-2 was significantly upregulated, while the expression of Cyt-c, Bax, and cleaved-caspase-3 was notably downregulated. GHI administration attenuated the pathological change and morphology of the cerebral microvasculature, and immunohistochemical staining indicated that the expressions of BFGF, VEGF, and TGF-β1 were significantly increased. The cell morphology, cell viability, cell nuclei characteristics, and mitochondrial morphology normalized following GHI treatment, which decreased the release of Cyt-c and the mitochondrial membrane potential. The levels of LDH, MMP-9, and MDA decreased, while SOD increased. Moreover, GHI administration inhibited the activation of the PI3K/AKT signaling pathway in rat brain microvascular endothelial cells (rBMECs) following oxygen/glucose deprivation (OGD) injury. Therefore, our results show that GHI administration resulted in anti-apoptosis of cerebral cells and repair of cerebral microvessels and mitochondria via the PI3K/AKT signaling pathway.